Amorphous carbonates as precursors of dolomite and magnesite in caves - Sarah Bonilla-Correa; Encarnación Ruiz-Agudo; Concepción Jiménez de Cisneros; Cristina Liñán Baena; Isabel Sánchez-Almazo; Carlos Rodriguez-Navarro; Maria P. Asta (Geochimica et Cosmochimica Acta, 2026)

Soil refrigeration and air-drying preserve sensitivity of aminopeptidase activities to long-term nitrogen fertilization - Chammi P. Attanayake; Sara Eldessouky; Katie Indorante; Ivanellis Rodriguez-Torres; Ekundayo Adeleke; Maria B. Villamil; Andrew J. Margenot (Biology and Fertility of Soils, 2026)
Evaluating soil storage impacts on aminopeptidase activity can inform the use of aminopeptidase activity in soil N cycling assessments. We evaluated the impact of soil refrigeration (4 °C) and air-drying relative to field-fresh (4 °C for ≤ 3 d) on the activities and sensitivity of eight amino acid-specific aminopeptidase activities across a 42 y N fertilization gradient (0–269 kg N ha − 1 ) over 1.5, 6, 12 and 24 mo storage. Soil storage generally decreased (7–95%) or did not impact aminopeptidase activities, but in some cases increased activity (7–18%). Activity decreases were greatest for glutamic acid, arginine, and lysine aminopeptidases. Proline and leucine aminopeptidase activities were least impacted by soil storage. In field-fresh soils, only arginine and lysine aminopeptidase activities differed across the N fertilization gradient: ≈50% lower at the second highest (202 kg N ha − 1 ) relative to the lowest (67 kg N ha − 1 ) positive fertilization rate, a trend preserved for up to 12 mo in refrigerated soils and up to 24 mo in air-dried soils. Aminopeptidase activities that were similar across the N fertilization gradient in field-fresh soils also remained similar in stored soils, or responded similarly to N fertilization as arginine and lysine aminopeptidase activities. Most aminopeptidase activities were similar between refrigerated and air-dried soils for at least 6 mo or up to 24 mo. Though soil storage impacts on activities were aminopeptidase-specific, both storage methods preserved the sensitivity of aminopeptidase activities to long-term field N fertilization treatments.

Optimism predicts future economic mobility among hurricane maria migrants - Maria Duque; Yara Acaf; Christopher P. Salas-Wright; Mildred M. Maldonado-Molina; Pablo Montero-Zamora; Evelyn Gualdron; Mia Cisco; Sumeyra Sahbaz; Carolina Scaramutti-Gladfelter; Lawrence G. Watkins; Duyen H. Vo; Seo Woo Lee; et al. (Climate and Development, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Integrative systematics of the Brazilian tree “sucupira”: morphological, cytogenetic and genomic boundaries of Pterodon emarginatus Vogel and P. pubescens (Benth.) Benth. (Leguminosae, Papilionoideae) - Victória B. Albernaz; Yennifer Mata-Sucre; Mariela A. Sader; Pablo E. Rodriguez; Cíntia P. Targueta; Adriana M. Antunes; Rafael B. Pinto; André Marques; Dulce Maria Sucena D. A. Rocha; Gustavo Souza; Thannya N. Soares (Systematics and Biodiversity, 2025)

Optimistic climate mitigation scenario halves projected range loss in a neotropical dolphin - Rodrigo Tardin; Guilherme Maricato; Jeremy J. Kiszka; Mauricio Cantor; Israel Maciel; Gabriel Melo-Santos; Laura May-Collado; Ana Carolina Meirelles; Maria Isabel C. Gonçalves; Fábio G. Daura-Jorge; Renata S. Sousa-Lima; Yvonnick Le Pendu; et al. (Ocean & Coastal Management, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Promoting Workplace Health, Safety, and Well-Being Among Essential Agricultural Workers Through Vaccine-Preventable Infectious Diseases Training in the Rio Grande Valley - Anabel Rodriguez; David I Douphrate; Ana L Pineda Reyes; Susana Zavala; Andrea V. Cabrera Cruz; Maria D Alegria; Brian Ukaegbu; Annie J Keeney; Brenda Berumen-Flucker; Eva M Shipp; Shannon P Guillot-Wright; Maria E Fernandez-Esquer; et al. (Journal of Agromedicine, 2025)

Coral-killing and competitive sponges in Nusa Dua, Bali, Indonesia - Dwi Haryanti; Alifalah T. Cahyadi; Fitri F.N. Al Haliim; Hafidza Mahira; Erin Karissa; Anindya Wirasatriya; Pariama Hutasoit; Diah P. Wijayanti; Munasik Munasik; Maria V. Baria-Rodriguez; Ardiansyah D. Puryajati (Regional Studies in Marine Science, 2024)

A coupled atmospheric simulation chamber system for the production of realistic aerosols and preclinical model exposure - Maria P. Georgopoulou; Juan Camilo Macias Rodriguez; Céline-Hivda Yegen; Christos Kaltsonoudis; Mathieu Cazaunau; Christina N. Vasilakopoulou; Angeliki Matrali; Katerina Seitanidi; Andreas Aktypis; Athanasios Nenes; Clément Buissot; Aline Gratien; et al. (Air Quality, Atmosphere & Health, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Assessing the nitrogen supply of hairy vetch in a soybean-wheat sequence - Maria P. Rodriguez; Ana J.P. Carcedo; Adrian A. Correndo; Cecilia Crespo; Walter D. Carciochi; Hernan R. Sainz Rozas; Ignacio A. Ciampitti; Pablo A. Barbieri (Field Crops Research, 2024)

Ataxia-telangiectasia in Latin America: clinical features, immunodeficiency, and mortality in a multicenter study - Renan A. Pereira; Ellen O. Dantas; Jessica Loekmanwidjaja; Juliana T. L. Mazzucchelli; Carolina S. Aranda; Maria E. G. Serrano; Elisabeth A. De La Cruz Córdoba; Liliana Bezrodnik; Ileana Moreira; Janaira F. S. Ferreira; Vera M. Dantas; Valéria S. F. Sales; et al. (Immunologic Research, 2024)

Short-term effects of air pollution and weather on physical activity in patients with chronic obstructive pulmonary disease (COPD) - Alícia Josa-Culleré; Xavier Basagaña; Sarah Koch; Ane Arbillaga-Etxarri; Eva Balcells; Magda Bosch de Basea; Nuria Celorrio; Maria Foraster; Robert Rodriguez-Roisin; Alicia Marin; Gabriela P. Peralta; Diego A. Rodríguez-Chiaradia; et al. (Environmental Research, 2024)

The Colombian geochronological database (CGD) - Andres F. Rodriguez-Corcho; Yamirka Rojas-Agramonte; Johana A. Barrera-Gonzalez; Maria P. Marroquin-Gomez; Sarah Bonilla-Correa; David Izquierdo-Camacho; Sofia M. Delgado-Balaguera; David Cartwright-Buitrago; Maria D. Muñoz-Granados; William G. Carantón-Mateus; Alejandro Corrales-García; Andrés F. Laverde-Martinez; et al. (International Geology Review, 2022)

“Right diet for the right person”: a focus group study of nutritionist-dietitians’ perspectives on nutritional genomics and gene-based nutrition advice - Jacus S. Nacis; Marilou R. Galang; Jason Paolo H. Labrador; Milflor S. Gonzales; Aurora Maria Francesca D. Dablo; Diana Glades A. Domalanta-Ronquillo; Victor Franco J. Alfonso; Idelia G. Glorioso; Marietta P. Rodriguez (Journal of Community Genetics, 2022)
Advances in nutritional genomics are intended to revolutionize nutrition practice. A basic understanding of nutritional genomics among nutritionist-dietitians is critical for such advancements to occur. As a precedent to the development and integration of gene-based nutrition advice, this study aimed to assess hospital-based nutritionist-dietitians’ perceptions of nutritional genomics. A total of ten focus group discussions (FGDs) with sixty-one registered nutritionist-dietitians (RNDs) from hospitals in the National Capital Region (NCR), Philippines, were conducted from October to November 2019. Data were collected using a pretested semistructured discussion guide, and thematic analysis was subsequently performed. Diverging perceptions about nutritional genomics were noted among the FGD participants. Five themes emerged relating to the enablers and barriers of gene-based nutrition advice: training and capacity building, the extent of information to be disclosed, cost, ethical considerations, and government support. Themes related to the desired features of the gene-based nutrition advice included being consent-driven, cost-effective, technology-oriented, and guided by standards. The results of this study suggest that training and continued learning will equip RNDs to provide nutrition advice based on genetic information. However, other factors, such as cost and ethical considerations, are critical dimensions that need to be acknowledged and addressed before integrating gene-based advice into nutrition practice.

Spatial and Short-Term Temporal Patterns of Octocoral Assemblages in the West Philippine Sea - Jue Alef A. Lalas; Romina Therese S. Lim; Joey P. Cabasan; Christine S. Segumalian; Rhea Mae A. Luciano; Darryl Anthony M. Valino; Melchor R. Jacinto; Hazel O. Arceo; Maria Vanessa Baria-Rodriguez (Frontiers in Marine Science, 2022)
Octocorals are relatively understudied than other coral reef organisms despite their ecological and economic values. The Philippines is known to have high marine biodiversity, but information on octocorals is lacking. This study investigated spatial and temporal variations in the assemblage of octocorals in selected reef sites in the West Philippine Sea (WPS)- the Kalayaan Island Group (i.e., Pag-asa, Sabina, Lawak, and Northeast Investigator) and Ulugan in 2017 and 2019. Results showed high octocoral taxonomic richness (at least 10 families) in the study sites. Mean percent octocoral cover in WPS was 5.35% SE ± 0.55, with Sabina having the highest octocoral cover in both years. Significant differences in octocoral cover were observed among sites in both years, but among-station differences were only observed in 2017. Octocoral assemblage also differed among sites in both years (ANOSIM: R > 0.5, p < 0.05), wherein different octocoral taxa dominated in different sites. In particular, variations were driven by high cover of holaxonians, nephtheids, and coelogorgiids in Sabina, and clavulariids, tubiporiids, and xeniids in Northeast Investigator in 2017. In 2019, significant variations were driven by high cover of helioporiids in Pag-asa, while Sabina had higher abundance of holaxonians, nephtheids, alcyoniids, and xeniids. Short-term temporal variation on octocoral cover in monitoring stations in Pag-asa was not observed (Kruskal-Wallis, p > 0.05), although the overall mean octocoral cover increased from 1.23% ± SE 0.47 in 2017 to 2.09% SE ± 0.37 in 2019. Further, there was no significant change in the octocoral assemblage in Pag-asa between years (ANOSIM, R = 0.11, p = 0.07). This study highlights high octocoral taxonomic richness in the WPS relative to other sites in the Indo-Pacific Region and provides baseline information on the octocoral assemblages, which can be useful for future ecological studies and marine biodiversity conservation efforts.

Pursuing Multiple Biomarkers for Early Idiopathic Parkinson’s Disease Diagnosis - Yareth Gopar-Cuevas; Ana P. Duarte-Jurado; Rosa N. Diaz-Perez; Odila Saucedo-Cardenas; Maria J. Loera-Arias; Roberto Montes-de-Oca-Luna; Humberto Rodriguez-Rocha; Aracely Garcia-Garcia (Molecular Neurobiology, 2021)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Adenovirus-Mediated Transduction of Insulin-Like Growth Factor 1 Protects Hippocampal Neurons from the Toxicity of Aβ Oligomers and Prevents Memory Loss in an Alzheimer Mouse Model - Maria Clara Selles; Juliana T. S. Fortuna; Maria F. Zappa-Villar; Yasmin P. R. de Faria; Amanda S. Souza; Claudia K. Suemoto; Renata E. P. Leite; Roberta D. Rodriguez; Lea T. Grinberg; Paula C. Reggiani; Sergio T. Ferreira (Molecular Neurobiology, 2020)

Autophagy Stimulation Decreases Dopaminergic Neuronal Death Mediated by Oxidative Stress - Marcela J. Ramirez-Moreno; Ana P. Duarte-Jurado; Yareth Gopar-Cuevas; Alfredo Gonzalez-Alcocer; Maria J. Loera-Arias; Odila Saucedo-Cardenas; Roberto Montes de Oca-Luna; Humberto Rodriguez-Rocha; Aracely Garcia-Garcia (Molecular Neurobiology, 2019)

Toward the Integrated Marine Debris Observing System - Nikolai Maximenko; Paolo Corradi; Kara Lavender Law; Erik Van Sebille; Shungudzemwoyo P. Garaba; Richard Stephen Lampitt; Francois Galgani; Victor Martinez-Vicente; Lonneke Goddijn-Murphy; Joana Mira Veiga; Richard C. Thompson; Christophe Maes; et al. (Frontiers in Marine Science, 2019)

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

PTRF acts as an adipokine contributing to adipocyte dysfunctionality and ectopic lipid deposition - Sergio Perez-Diaz; Maria P. Garcia-Sobreviela; Yolanda Gonzalez-Irazabal; Beatriz Garcia-Rodriguez; Silvia Espina; Izaskun Arenaz; Jose M. Arbones-Mainar (Journal of Physiology and Biochemistry, 2018)

A Catalogue of Marine Biodiversity Indicators - Heliana Teixeira; Torsten Berg; Laura Uusitalo; Karin Fürhaupter; Anna-Stiina Heiskanen; Krysia Mazik; Christopher P. Lynam; Suzanna Neville; J. German Rodriguez; Nadia Papadopoulou; Snejana Moncheva; Tanya Churilova; et al. (Frontiers in Marine Science, 2016)

Differential gene transcription, biochemical responses, and cytotoxicity assessment in Pacific oyster Crassostrea gigas exposed to ibuprofen - Miguel A. S. Serrano; Maria Gonzalez-Rey; Jacó J. Mattos; Fabrício Flores-Nunes; Álvaro C. P. Mello; Flávia L. Zacchi; Clei E. Piazza; Marília N. Siebert; Rômi S. Piazza; Diana Alvarez-Muñoz; Sara Rodriguez-Mozaz; Damià Barceló; et al. (Environmental Science and Pollution Research, 2015)

Cosmogenic nuclide exposure ages from the ‘Parallel Roads’ of Glen Roy, Scotland - Derek Fabel; David Small; Maria Miguens‐Rodriguez; Stewart P. H. T. Freeman (Journal of Quaternary Science, 2010)
The ‘Parallel Roads’ of Glen Roy, Scotland, are the shorelines of former ice‐dammed lakes created by the last glaciers to occupy the area. We use surface exposure dating with cosmic ray‐produced 10 Be in quartz to provide the first numerical age control on the timing of formation of one of one of these shorelines and depositional features in Glen Roy. Four bedrock samples from the surface of the 325 m ‘Parallel Road’ yielded a mean formation age of ca. 11.5–11.9 ka. This age range confirms the long‐held view that the ‘Parallel Roads’ are Loch Lomond Stadial (ca. 12.9–11.5 ka) features. The age range reflects variation in currently available cosmogenic nuclide scaling schemes and the related 10 Be production rates. Two samples from the surface of the Turret fan indicate that the 260 m lake drained before ca. 10.7–11.0 ka, while two samples from the Brunachan fan suggest that subaerial sedimentation occurred after ca. 9.7–9.9 ka. Copyright © 2009 John Wiley & Sons, Ltd.

Methamphetamine Enhances HIV-1 Infectivity in Monocyte Derived Dendritic Cells - Madhavan P. N. Nair; Zainulabedin M. Saiyed; Narayanan Nair; Nimisha H. Gandhi; Jose W. Rodriguez; Nawal Boukli; Elias Provencio-Vasquez; Robert M. Malow; Maria Jose Miguez-Burbano (Journal of Neuroimmune Pharmacology, 2009)

Physical and chemical processes in the application of CA and/or fumigation - Cecilia V. De Dios; Maria Finesa A. Cosico; Ma. Elvira M. Martinez; D. D. Julian; I. V. Dator; R. L. Tiongson; J. van S. Graver; S. Pratt; C. Reed; Sylvia Allen; G. N. Mbata; T. W. Phillips; et al. (Phytoparasitica, 2001)

Death and neuroprotection of retinal ganglion cells after different types of injury - Manuel Vidal-Sanz; Maria Lafuente; Paloma Sobrado-Calvo; Inmaculada SellÉs-Navarro; Elena Rodriguez; Sergio Mayor-Torroglosa; MarÍa P. Villegas-PÉrez (Neurotoxicity Research, 2000)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)